PELATIHAN PENGGUNAAN METODE TOTAL PHYSICAL RESPONSE DAN NATURAL APPROACH DALAM PENGAJARAN BAHASA INGGRIS DI LEMBAGA PENDIDIKAN ACTIVE ENGLISH COURSE - Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
AbstractThe activity of community service that was held in Active English Course Institution which is addressed in Grand Depok City Ruko Anggrek D1 No. 4 had the aims; they are giving a training which contains of deliberate knowledge and information of Total Physical Response Method and Natural Approach that both can be used on teaching English especially on young learners level. This community service activity was applied on such kind of training that was proposed to the teachers in Active English Course Institution who mostly teach to primary school student. The activity was implemented by using a Communicative Language Teaching Method that it was processed by having a discussion communicatively whether from the speakers and the audience. This community service was held for four months that was began from October 2015 to January 2016.Key words: Total Physical Response Method, Natural approach, and Teaching English